FEATURES OF LABOR MOBILITY OF THE DOMESTIC LABOR MARKET IN THE CONTEXT OF MODERN REFORMS - Жеребило, Ірина (Socio-economic relations in the digital society, 2020)
The article deals with the problem of mass migration of labor resources from Ukraine abroad in the context of modern reforms, which are accompanied by high unemployment, increased social tension and increased differentiation in the standard of living of the population. The peculiarities of labor migration to other countries have been investigated and the factors that stimulate this process in Ukraine have been identified. The problem of migration of highly skilled personnel is emphasized and the difference of goals and reasons forleaving of highly skilled and low skilled personnel is substantiated. In the first case, it is the prospect of using quality institutions, career development and a sense of security; the second is earnings. The main tendencies that characterize the process of external labor migration from Ukraine under the present conditions are identified and characterized. Among the results of the migration patterns of Ukrainians abroad in recent years are the following: the vast majority of migrants are representatives of the most simple professions and skilled workers with the tool; there is an active involvement of young people in migration processes and an increased risk of non-return due to the lack and low level of social networking. Today, there is a decrease in the length of stay of migrants abroad. This demonstrates the growth of circular migration and re-emphasizes the problem of employment policy inefficiency in Ukraine. To overcome these obstacles, it is first necessary to make systemic changes in the field of training and improve the quality of education, as well as to ensure the attractiveness of certain professions through increased wages. Therefore, we need a new look at the education system in Ukraine and the formation of the relationship between the development of education and the labor market, bringing them into line with the needs of the economy.
Keywords: external labor migration; labor migrants; qualification and professional characteristics; motives for migration